Integrated Metabolomics and Network Pharmacology Analysis Immunomodulatory Mechanisms of Qifenggubiao Granules - Guo, Bindan; Dong, Wenting; Huo, Jinhai; Sun, Guodong; Qin, Zhiwei; Liu, Xiaodong; Zhang, Bihai; Wang, Weiming (Frontiers in Pharmacology, 2022)
Background: Qifenggubiao granules (QFGBG) is a new Chinese medicine independently developed by Heilongjiang Academy of Traditional Chinese Medicine, which combines the essence of Yupingfeng powder and Shengmai yin (invention patent number: CN1325098C, approval number: Sinopharm Zhunzi B20020410), and has been included in the 2020 edition of Chinese Pharmacopoeia. It has remarkable pharmacodynamic results and conclusive clinical effects in the treatment of allergic rhinitis, chronic cough and other diseases. Previous pharmacological studies have shown that it has immunomodulatory effect, but its immunomodulatory mechanism is still unclear. Methods: In this study, cyclophosphamide (CTX) was used to establish the immune hypofunction model in mice, and the weight change, index of immune organs in spleen and thymus, pathological sections of immune organs and inflammatory factors were used to evaluate the model. Based on the metabolic biomarkers obtained by metabonomics technology, the potential targets of Qifeng Gubiao Granule immunomodulation were obtained by integrating the targets of blood components, metabolites and diseases through network pharmacology. Meanwhile, GO enrichment analysis and KEGG pathway analysis were carried out on the potential targets. Results: QFGBG can increase body weight and organ index, and recover immune organ damage caused by CP. Metabonomics identified 13 metabolites with significant changes, among which the level of phospholipid (PC) metabolites decreased significantly in the model group. Sphingosine -1- phosphate, 1- palmitoyl phosphatidylcholine [LysoPC (16:0/0:0)] and other metabolites were significantly increased in the model group, and 98 targets of Qifeng’s external immune regulation were obtained by intersecting 629 component targets, 202 metabolite targets and 1916 disease targets. KEGG pathway analysis obtained 233 related metabolic pathways, and the top 20 metabolic pathways mainly involved IL-17 signaling pathway, TNF signaling pathway, Sphingolipid signaling pathway, and so on. Conclusion: QFGBG may act on AKT1, IL6, MAPK3, PTGS2, CASP3, MAPK1, ESR1, PPARG, HSP90AA1, PPARA and other targets, acting through Sphingolipid signaling pathway and signaling pathway. Combined with pharmacodynamic evaluation, the immunomodulatory effect of QFGBG was confirmed, and the immunomodulatory mechanism of QFGBG with multiple targets and multiple pathways was preliminarily clarified.